(untitled) (Acta Entomologica Serbica, 2020)
Field surveys were carried out in the provinces of Balıkesir, Bilecik, Bursa, Çanakkale, Edirne, İstanbul, İzmit, Kırklareli, Sakarya, Tekirdağ and Yalova in the Marmara region of Turkey between 2009 and 2010. As a result of identification of the collected specimens, 17 genera and 31 species, belonging to Diaphorinae, Dolichopodinae, Hydrophorinae, Rhaphininae, Sciapodinae, Sympycninae, Xanthochlorinae subfamilies, were determined. Two species (Hercostomus plagiatus Loew, 1857 and Poecilobothrus nobilitatus Linnaeus, 1767) are new records for Turkey dolichopodid fauna.